Annotated legal documents on Islam in Europe : Czech Republic - Němec, Damián 1960-; Hesová, Zora 1974- (Boston Brill, 2021)
Foreword by the Editors -- General Introduction -- 1. Status of Religious Communities -- 2. Relations between the State and Islam -- 3. State Support for Islamic Religious Communities -- 4. The Islamic Community of the Czech Republic -- 5. Muslims and the Law on Issues of Social Integration -- 6. Mosques and Prayer Houses -- 7. Burial and Cemeteries -- 8. Education and Schools -- 9. Further and Higher (Tertiary) Education -- 10. Islamic Chaplaincy in Public Institutions -- 11. Employment and Social Law -- 12. Islamic Slaughter and Food Regulation -- 13. Islamic Goods and Services -- 14. Islamic Dress -- 15. Criminal Law -- 16. Family Law -- Bibliography -- Index.
"This volume of Annotated Legal Documents on Islam in Europe covers the Czech Republic and consists of an annotated collection of legal documents affecting the status of Islam and Muslims. The legal texts are published in the original Czech language while the annotations and supporting material are in English. By legal documents are meant the texts of legislation, including relevant secondary legislation, as well as significant court decisions. Each legal text is preceded by an introduction describing the historical, political and legal circumstances of its adoption, plus a short paragraph summarising its content. The focus of the collection is on the religious dimensions of being Muslim in Europe, i.e. on individuals' access to practise their religious obligations and on the ability to organise and manifest their religious life"--
Includes bibliographical references and index
Keywords: Muslims -- Legal status, laws, etc -- Czech Republic; Minorities -- Legal status, laws, etc -- Czech Republic